Isolation and Identification of Chromium-Tolerant Bacteria from Poultry Litter in Dhaka, Bangladesh (Stamford Journal of Microbiology, 2024)
Tannery waste, known for its high chromium content, often contaminates chicken feed, accumulating chromium in chickens and their excreted waste. This study aimed to isolate chromium-tolerant bacteria from chicken litter and evaluate their ability to withstand various chromium concentrations. Four bacterial isolates—CM3, CM4, CM5, and CM6 were presumptively identified as Pseudomonas sp., Bacillus sp., Staphylococcus sp., and Bacillus sp., respectively. The isolate CM4 showed the highest tolerance, growing at 800 mg/L concentrations. A subsequent experiment focused on CM4, where growth was measured by absorbance at 600 nm across chromium concentrations from 0 mg/L to 3200 mg/L. The results indicated a significant decrease in growth with increasing chromium levels, with near-complete inhibition at the highest concentrations. This study highlights the potential of chromium-tolerant bacteria from poultry litter for bioremediation, particularly in environments contaminated with this heavy metal. These findings contribute to ongoing efforts to mitigate chromium pollution through microbial interventions.Stam. J. Microbiol. 2024;14(1):18-21